Miniature high sensitive pH sensor based on micro optical fiber interferometer - Oon, Roy Guo Hao (2017)
A biocompatible pH sensor based on a Mach-Zehnder is proposed with the structure of SMF-TCF-SMF with a taper on the TCF portion. The sensor is then coated with PVA/PAA hydrogel which swells reversibly in response to changes to pH, which leads to a change of refractive index which translate to shifting interference dips in the optical spectrum analyzer. The proposed sensor has limited success with a sensitivity of 0.73449 and R2= 0.8947. The range of sensitivity was between pH 2 to 4.2.